A Case Study of Process Intervention within the Enterprise Content Management System Support Process. Issue 1 (12th January 2018) - Pate, Caitlin; Spangler, Aimee; Strawn, Nikki; Pastore, Ray
Abstract: A global clinical research organization consisting of over 20, 000 employees wants to reduce resources needed to maintain support of an enterprise‐wide online document repository. The organization would like to implement processes that would allow their technology and support groups to transition from a reactive state of end‐user support to a proactive state and cultivate a culture of self‐supporting end users, thus reducing the daily number of tickets submitted for IT assistance over the next 12 months.